Signal Processing Algorithms for Down-Stream Traffic in Next Generation 10 Gbit/s Fixed-Grid Passive Optical Networks. (22nd June 2014) - Asif, Rameez; Basir, Rabeea; Ahmad, Ramshah
Abstract : We have analyzed the impact of digital and optical signal processing algorithms, that is, Volterra equalization (VE), digital backpropagation (BP), and optical phase conjugation with nonlinearity module (OPC-NM), in next generation 10 Gbit/s (also referred to as XG) DP-QPSK long haul WDM (fixed-grid) passive optical network (PON) without midspan repeaters over 120 km standard single mode fiber (SMF) link for downstream signals. Due to the compensation of optical Kerr effects, the sensitivity penalty is improved by 2 dB by implementing BP algorithm, 1.5 dB by VE algorithm, and 2.69 dB by OPC-NM. Moreover, with the implementation of NL equalization technique, we are able to get the transmission distance of 126.6 km SMF for the 1 : 1024 split ratio at 5 GHz channel spacing in the nonlinear region.